Neonatologist Performed Echocardiography for Evaluating the Newborn Infant - Nestaas, Eirik (Frontiers in Pediatrics, 2022)
The interest in use of cardiac ultrasound for hemodynamic evaluation in neonates has increased the last decades. Several overlapping terms exists, and a non-comprehensive list includes Point-Of-Care Ultrasound, Clinician Performed Ultrasound, Focused Cardiac Ultrasound, Targeted Neonatal Echocardiography and Neonatologist Performed Echocardiography. This review will use the term Neonatologist Performed Echocardiography. Neonatologist Performed Echocardiography is primarily echocardiography to obtain snapshots of hemodynamics and heart function, usually as repeated exams during intensive care. It provides the neonatologist with in-depth information on the hemodynamics not available by blood pressure, pulse oximetry, capillary refill time and various blood tests. The review provides a brief overview of some relevant methods for assessment of hemodynamics and heart function. It does not discuss training, implementation, accreditation and certification nor in-depth technical aspects and detailed of use of Neonatologist Performed Echocardiography. If the information obtainable by Neonatologist Performed Echocardiography had been accessible easily (e.g. via a sensor put on the neonate similarly to a pulse oximeter), Neonatologist Performed Echocardiography would have been more widely used. Acquiring skills for Neonatologist Performed Echocardiography take time and resources. Future developments probably include a stronger focus on education, training and certification. It is likely that echocardiographic methods will evolve further, probably involving establishing new indexes and methods, and implementing artificial intelligence in the analyses procedure to improve accuracy and workflow. It is important to acknowledge that Neonatologist Performed Echocardiography is not a therapeutic intervention; it is a diagnostic tool providing additional information.